Unrecognized threat to global soil carbon by a widespread invasive species. (19th July 2021) - O'Bryan, Christopher J.; Patton, Nicholas R.; Hone, Jim; Lewis, Jesse S.; Berdejo‐Espinola, Violeta; Risch, Derek R.; Holden, Matthew H.; McDonald‐Madden, Eve
Abstract: Most of Earth's terrestrial carbon is stored in the soil and can be released as carbon dioxide (CO2 ) when disturbed. Although humans are known to exacerbate soil CO2 emissions through land‐use change, we know little about the global carbon footprint of invasive species. We predict the soil area disturbed and resulting CO2 emissions from wild pigs ( Sus scrofa ), a pervasive human‐spread vertebrate that uproots soil. We do this using models of wild pig population density, soil damage, and their effect on soil carbon emissions. Our models suggest that wild pigs are uprooting a median area of 36, 214 km 2 (mean of 123, 517 km 2 ) in their non‐native range, with a 95% prediction interval (PI) of 14, 208 km 2 –634, 238 km 2 . This soil disturbance results in median emissions of 4.9 million metric tonnes (MMT) CO2 per year (equivalent to 1.1 million passenger vehicles or 0.4% of annual emissions from land use, land‐use change, and forestry; mean of 16.7 MMT) but that it is highly uncertain (95% PI, 0.3–94 MMT CO2 ) due to variability in wild pig density and soil dynamics. This uncertainty points to an urgent need for more research on the contribution of wild pigs to soil damage, not only for the reduction of anthropogenically related carbon emissions, but also for co‐benefits to biodiversity and food security that are crucial for sustainable development. Abstract : We predict soil damage and resulting CO2 emissions from invasive wild pigs ( Sus scrofa ). We find that their median disturbed area is 36, 214 km 2, with corresponding emissions of nearly five million metric tonnes (MMT) CO2 per year (equivalent to one million passenger vehicles). However, our estimates are highly uncertain (PI, 0.3–94 MMT CO2 ), pointing to an urgent need for more research on the contribution of wild pigs to soil damage. This is important not only for the reduction of carbon emissions, but also for co‐benefits to biodiversity and food security that are critical for sustainable development.